STUDI KOMPARASI MODEL PEMBELAJARAN PAI ANTARA PESERTA DIDIK PROGRAM UNGGULAN DAN SMART TAHFIZ KELAS 1 MINU TRATE PUTRI GRESIK - Siti Amaliati, Anisatul Mahbubah, (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2020)
ABSTRACT   The article is for to find out how the learning model applied at MINU Trate Putri Gresik. the object of this article at MINU Trate Putri Gresik. its to compare the learning model applied in the exellent class program with the first class smart Tahfiz program. This research, for review about studying in Madrasas, and researchers get for a good information about it and the learning process in the exellent program and Smart Tahfiz programs and it use different learning processes. It this have a differences in the learning model. Which in the exellent program uses the model in general, while the program Smart Tahfiz learning to use a model that has been added to the study of the Qur'an. These two programs differ, the learning model of each program for students must be different. The result of the learning model that can be seen directly is the difference between the students patterns in each activity in the school.  To search for definitive data on this article using interviews, observation and documentation data collection techniques. Observers, saw the learning process and compared the learning models in the exellent program and the Smart Tahfiz program. And from the author's observations that the learning model of these two programs is almost the same but different in the process of teaching.   Keyword: Learning model, exellent program, Smart Tahfiz Program